Representasi Keluarga dalam Konteks Hukum Islam - Anung Al Hamat (Program Studi Hukum Keluarga Islam, 2017)
The family is built from the ties between two different beings and then be allied in a marriage. Marriage oriented to form a sakinah family, which is based on love and affection. Marriage is a strong commitment between fellow brides. The family is in human experience.In relation with Islamic law, the family has a strategic position. Legal arrangements for individuals and families are closely linked to the awareness and religious adherence of each Moslem. With the formation of a family, it will automatically rise a law in it. Where this law contains a rule that is charged to all family members.There are several inherent goals in each marriage those are (1) justifying the sexual relationship to satisfy the intent of human character, (2) realizing a family with the basis of love, love and (3) obtaining a legitimate generation.Family has a very important function in individuals forming. Therefore, the whole function must be kept in mind. If one of these functions does not perform, so there will be disharmony in the system of rule in the family.